Outcome of Suprachoroidal Triamcinolone Acetonide in Resistant Diabetic Macular Edema: Resistant Diabetic Macular Edema - Jamil, Muhammad Hannan; Ashraf, Aneeb; Khan, Asmatullah; Ashraf, Bilal; Afzal, Muhammad Bilal; Shahbaz , Ferheen (Pakistan Journal of Health Sciences, 2023)
One of the most frequent cause of central vision deterioration in people with retinopathy due to diabetes is diabetic macular edema. Suprachoroidal injections offer a novel way of delivery for the administration of corticosteroids that may have various benefits. Objective: To observe outcome of triamcinolone acetonide given by suprachoroidal route for the treatment of resistant diabetic macular edema. Methods: A descriptive case series study which was carried out at Department of Ophthalmology, Layton Rahmatullah Benevolant Trust Hospital Multan Road Lahore from July 14, 2021 till Jan 14, 2022. A total of 60 cases meeting selection criteria was taken after taking approval from hospital ethical committee. All injections were given by a single surgeon to avoid any related bias. 30-gauge 1cc insulin syringe was used in all cases. Results: The study included patients aged between 30 and 70 years, and the average age was 52.73 ± 10.99 years. There were 39(65%) male with 21(35%) female cases. The average central subfield thickness before and after one month was 593.62 ± 116.87 µm and 303.55 ± 31.29 µm with statistically significantly less mean central subfield thickness after 1 month, p-value less than 0.001. The mean visual acuity after correction before and after one month was 0.81 ± 0.16 and 0.45 ± 0.03 respectively, with statistically significantly less mean optimally corrected visual acuity after 1 month, p-value less than 0.001. Conclusions: It was found that suprachoroidal triamcinolone acetonide is useful in managing the central subfield and optimally corrected visual acuity in resistant diabetic macular edema.